2018
DOI: 10.7150/thno.24183
|View full text |Cite
|
Sign up to set email alerts
|

“Albumin Hitchhiking” with an Evans Blue Analog for Cancer Theranostics

Abstract: Although 177Lu-DOTA-TATE was recently approved in Europe for the treatment of certain neuroendocrine tumors, continued development and optimization has been ongoing to further improve the therapeutic efficacy of somatostatin receptor 2 targeted peptide receptor radionuclide therapy, as well as reducing the renal toxicity. In this work, the use of an Evans blue analog for “albumin hitchhiking” resulted in significant improvement in both the imaging performance and therapeutic efficacy of radiolabeled octreotate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Here, we report a K D for human ACE2 that has an affinity that is 1,000-fold higher than for human albumin ( K D , 1.6 nM; see Table 1 ). A recent review has detailed the potential for Evans blue in biomedical applications ( 50 ), including imaging in cancer ( 51 , 52 ). Vero-E6 cell infection assays for SARS-CoV-2 show that Evans blue has an IC 50 value of 28.1 μM, with a CC 50 of greater than 1 mM.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we report a K D for human ACE2 that has an affinity that is 1,000-fold higher than for human albumin ( K D , 1.6 nM; see Table 1 ). A recent review has detailed the potential for Evans blue in biomedical applications ( 50 ), including imaging in cancer ( 51 , 52 ). Vero-E6 cell infection assays for SARS-CoV-2 show that Evans blue has an IC 50 value of 28.1 μM, with a CC 50 of greater than 1 mM.…”
Section: Discussionmentioning
confidence: 99%
“…Most PRRT studies have focused on G1 and G2 NENs (6)(7)(8)(24)(25)(26)(27). The NETTER-1 study, a prospective randomized controlled phase 3 clinical trial using tandem treatment with 177 Lu-DOTA-TATE and octreotide (long-acting release) (30 mg) in patients with advanced midgut neuroendocrine tumors, also focused on well-differentiated NENs; in that study, a markedly improved PFS and a significantly higher response rate were reported with the tandem treatment than with high-dose octreotide (long-acting release) (6).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we developed a new class of small molecule albumin binding entities based on the long-circulating EB. EB displays a strong noncovalent binding with both murine and human serum albumin 37 - 40 . In our previous work, we have extensively studied the albumin binding abilities of EB conjugates with various chemical agents, and have confirmed their strong binding abilities 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%